Hukum Pembuatan Pupuk dari Bangkai Binatang - Rahmadani Rahmadani; Islahuddin Ramadhan Mubarak; Riska Riska; Nur Afni A. (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This study aims to find out and understand what the law of making fertilizer from animal carcasses is. The problems in this research are; First, how about the law of carrion in general? Second, how is the review of Islamic law on the manufacture of fertilizer from animal carcasses? Qualitative descriptive research (non-statistical) using historical approaches and normative juridical approaches. The data used in this study are sourced from primary data and secondary data in the form of the Koran, hadith, classic and contemporary books, journals, theses, papers, and scientific literature related to the title of this research. The results of the research found are first, the law on the use of animal carcasses is okay because it is also a treasure that can be used, what is forbidden from the carcass is consuming or eating it. Second, the review of Islamic law on the manufacture of fertilizer from animal carcasses is lawful because there has been suitability of each analytical review used, such as in terms of manufacture or production, qiyās, istitālah, and maslahah.